Modelagem de adequabilidade ambiental de nirodia belphegor (lepidoptera: riodinidae) - Glória Ramos Soares (2015)
The habitat loss and fragmentation currently are the main causes of extinctions. It is estimated than in few decades, several species may be extinct, especially endemic species, which have restricted geographic range occurring only in specific environmental to which they are well adapted. For these species habitat loss becomes the most influential factor in the population decline and vulnerability of extinction. Thus, this research aims to model the environmental suitability of Nirodia belphegor through seven modeling algorithms of environmental systems: Maximum Entropy, GARP, SVM and Environmental Distances (Mahalanobis, Euclidian, Gower and Chebyshev). The ensemble map, generated from models indicated the high altitude rocky complexes of Minas Gerais as appropriate areas for occurrence of N. belphegor . These regions are characterized by the high species richness of flora and fauna as well as rare and endemics, which often leads to a state of threatened. The conservation of these environments also promotes the maintenance of a large and significant historical and cultural heritage in the same region. The results of this research are offered for the scientific community in order to reinforce the need to conserve of N. belphegor and their occurrence, region, as well as areas higher suitability to harbor new populations, thus increasing your records and also to for contributing to the preservation of the high altitude rocky complexes of Minas Gerais.